Tourism Policy of Nepal and Sustainable Mountain Tourism Development in Retrospect - Upadhyay, Prakash (The Gaze: Journal of Tourism and Hospitality, 2019)
The modern history of tourism in Nepal began with mountain tourism embodying the diversity of nature and culture, diversity, marginality, access difficulty, fragility, niche and aesthetics. Despite huge scope, Nepal has been unable to take full benefits of mountains, due to inadequate policies and fragile implementation. Pedestaled on secondary data, the key objective of this paper is to make a retrospective assessment of tourism policy and sustainable mountain tourism development efforts in Nepal. The sustainable development of mountain tourism relies on the government’s plans and policies and the efficient coordination between stakeholders. But the tourism policies have not been able to adequately address mountain tourism, and this has led to unbalanced growth of tourism sector. Despite the implementation of new Tourism Policy in 2008, adequate focus on mountain tourism is still missing. There is a lacuna of adequate driving force in tourism policy and it has failed to address vital areas of mountain tourism. Hence, there is an instant need of specific and separate mountain tourism policy encompassing integrated approach (abiding federal structure and local participation in planning and management) hence making mountain tourism sustainable, responsible and sensitive–ecologically and culturally.